THE GROWTH STRATEGIES ANALYSIS OF TEN WOODY PLANT SPECIES FOR EFFECTIVE REVEGETATION - Ridesti Rindyastuti; Retno Peni Sancayaningsih (BIOTROPIA, 2018)
The growth strategies of plant species reflect their ecological roles, as expressed through their adaptations to environmental conditions and competitive abilities. These strategies are essential for evaluating the effectiveness of revegetation efforts. However, growth strategies of plant species across different habitat types have not been fully investigated. This study aimed to examine the growth strategies of ten woody plant species naturalized from mangrove to lowland habitats in relation to their effectiveness in revegetation programs. Seedling growth was monitored for four months at the Purwodadi Botanic Garden–LIPI from October 2014 to February 2015. A completely randomized design with plant species as treatments and three replications was applied to evaluate relative growth rates (RGRs), their components, leaf nitrogen productivity, and overall growth strategies. The results showed that RGRs varied among the ten woody plant species. Pearson correlation analysis indicated that net assimilation rate (NAR) and two root-related ecological traits—nitrogen productivity and specific root length (SRL)—were strongly correlated with RGR. Heritiera littoralis, Diospyros discolor, Antidesma bunius, Schleichera oleosa, Madhuca longifolia, and Syzygium cumini exhibited high RGRs but low specific leaf area (SLA). Barringtonia asiatica showed relatively low RGR and SLA, whereas Dracontomelon dao exhibited high RGR and SLA. These findings indicate that most of the studied species, except D. dao, achieve high growth rates and competitive ability by developing fine root systems that enhance nutrient uptake. Most woody species were well adapted to dry lowland habitats, while D. dao showed greater potential to dominate the ecosystem. Furthermore, D. discolor and S. oleosa are highly recommended for revegetation of degraded tropical lowland areas.